Micellar electrokinetic chromatography method for measuring amino acid secretions from islets of Langerhans. Issue 9 (May 2015) - Wang, Xue; Yi, Lian; Guillo, Christelle; Roper, Michael G.
Abstract : Electrophoresis 2015, 36, 1172–1178. DOI:10.1002/elps.201400569 Islets of Langerhans are responsible for maintaining glucose homeostasis through regulated secretion of hormones and other factors. It is hypothesized that amino acids secreted from islets play a critical role in cell functionality and viability. To characterize the potential roles that these small molecules may play in islet physiology, derivatization and MEKC separation conditions were optimized using D‐Norvaline as an internal standard. The cover image shows an electropherogram corresponding to the separation of amino acids released from 25 islets incubated in 3 mM glucose. Quantification of 14 amino acids was performed with LODs ranging from 0.2–7 nM. The effects of glucose and 2, 4‐dinitrophenol on amino acid secretions from islets were tested and a suppressive effect of glucose on GABA release was observed, likely acting through ATP inactivation of glutamate decarboxylase.